Identity authentication scheme of Android client based on identifiers - Ya-wei WANG; Chang-gen PENG; Hong-fa DING; Kai ZHOU (网络与信息安全学报)
The Android mobile terminal’s own identifier information was used,which was credibly ensured by the Android system,then combining the Hash function and operation such as xor or connection,an algorithm of authentication information generation for the Android client was created.The traditional mobile client’s process of register and login were analyzed,putting the identity information generation and authentication on the sever.A novel authentication scheme was constructed,which made the users free from the cumbersome authentication process and privacy divulges.Finally,the security and efficiency of the scheme were analyzed.The results show that the new scheme has strong security and high convenience.